2011
DOI: 10.1016/j.bcp.2010.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Human CYP2A6 is regulated by nuclear factor-erythroid 2 related factor 2

Abstract: Human CYP2A6 is responsible for the metabolism of nicotine and coumarin as well as the metabolic activation of tobacco-related nitrosamines. Earlier studies revealed that CYP2A6 activity was increased by dietary cadmium or cruciferous vegetables, but the underlying mechanisms remain to be clarified. In the present study, we investigated the possibility that Nrf2 might be involved in the regulation of CYP2A6. Real-time RT-PCR analysis revealed that the CYP2A6 mRNA level in human hepatocytes was significantly (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In the first step (phase I) drugs are functionalized to make them more reactive. The common reactions in this phase are oxidation, reduction or hydrolysis and are catalyzed by enzymes that can be induced by Nrf2, such as cytochrome P450 (Abu-Bakar et al, 2007;Yokota et al, 2011); aldoketo reductases (AKR) (Ellis, 2007) or NAD(P)H:quinone oxidoreductase 1 (NQO1) (Venugopal and Jaiswal, 1996), (considered a broad antioxidant and cytoprotector; Dinkova-Kostova and Talalay, 2010). During phase II detoxification, xenobiotics are subjected to conjugation with different polar compounds, such as glutathione (GSH), glucuronic acid or a sulfonic group.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step (phase I) drugs are functionalized to make them more reactive. The common reactions in this phase are oxidation, reduction or hydrolysis and are catalyzed by enzymes that can be induced by Nrf2, such as cytochrome P450 (Abu-Bakar et al, 2007;Yokota et al, 2011); aldoketo reductases (AKR) (Ellis, 2007) or NAD(P)H:quinone oxidoreductase 1 (NQO1) (Venugopal and Jaiswal, 1996), (considered a broad antioxidant and cytoprotector; Dinkova-Kostova and Talalay, 2010). During phase II detoxification, xenobiotics are subjected to conjugation with different polar compounds, such as glutathione (GSH), glucuronic acid or a sulfonic group.…”
Section: Introductionmentioning
confidence: 99%
“…Nongenetic factors contributing to this variability have been proposed, including administration of drugs, exposure to environmental chemicals, diet, and sex hormone (Al Koudsi et al, 2010). These can be partly explained by the activation of transcriptional factors such as pregnane X receptor (Itoh et al, 2006), glucocorticoid receptor (Onica et al, 2008), nuclear factorerythroid 2-related factor 2 (Yokota et al, 2011), and estrogen receptor (Higashi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a similar decrease in GSH levels was observed in ethanol-treated WT mice and cyp2a5 −/− mice; thus, other Nrf2-regulated mechanisms may be involved. CYP2A6, the human orthologue to CYP2A5, is regulated by Nrf2 (7, 30). Recently, we found that the ethanol induction of CYP2A5 occurs through a CYP2E1-ROS-Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 99%